Feedback - Sattamini, Isabela; Leitzmann, Claus; McMichael, Tony; Tudge, Colin; Burlingame, Barbara (World Nutrition, 2013)
Making WN interactive – please. By Isabela Sattamini The Giessen experience – the new nutrition science. By Claus Leitzmann, Tony McMichael, Colin Tudge Thanks to Philip James. By Barbara Burlingame